2007
DOI: 10.1007/bf02913324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of vitamin C and E on oxidative stress in osteoporosis

Abstract: Osteoporosis encompasses a wide spectrum of conditions associated with imbalance of osteoclastic and osteoblastic activities. The increased activity of osteoclasts leads to increased free radical formation and hence lipid peroxidation. Present study probes into the role of antioxidants as a palliative treatment for osteoporosis. It involved 50 healthy controls and 75 clinically diagnosed osteoporosis patients. Both the groups underwent baseline assessment of biochemical markers viz. osteoblastic markers: serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 8 publications
3
37
0
Order By: Relevance
“…Conversely, Li and colleagues had found no any effect of vitamin E supplementation on these enzymes activities [Li et al 1996]. Chavan and colleagues observed a significant rise in their activities only in combination with vitamin C supplementation [Chavan et al 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Li and colleagues had found no any effect of vitamin E supplementation on these enzymes activities [Li et al 1996]. Chavan and colleagues observed a significant rise in their activities only in combination with vitamin C supplementation [Chavan et al 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [20] have shown that lipid peroxidation was increased in osteoporosis due to oxidative stress. We were interested in measuring the status of antioxidant vitamin i.e.…”
Section: Resultsmentioning
confidence: 85%
“…Intervention studies show mixed results, which may be due to trial length. postmenopausal women receiving 10g/d oral vitamin C showed no effect on markers of bone turnover in a four week study 73 , although 1000mg/d given with 600mg/d vitamin e for six months showed a significant improvement in spine BMD 74 and 500mg/d vitamin C in combination with 400mg/d vitamin e for 90 days increased sod, gsh and osteoblastic markers in osteoporosis patients 10 . although humans have lost the ability to synthesis vitamin C, knock-out studies in animals show that vitamin C deficiency correlated with increased fracture risk, decreased expression of bone formation markers 75 and increased osteoclastogenesis by increasing expression of raNK 76 , while treatment generally reduced bone fragility and improved healing, BMd and osteoblastic survival 28,77 , while reducing lipid peroxidation and osteoclast differentiation, with decreasing NF-kappaB and raNKl expression 78 .…”
Section: Calcificationmentioning
confidence: 91%
“…Valabhji et al found that the inverse association between total antioxidant status and CaC became non-significant after adjustment for age and/or diabetes duration 22 , while a sod mimetic could reduce induced medial calcification in rats 23 but worsened aortic valve calcification 13 . Nevertheless, antioxidants can generally inhibit raNKl expression 8,9 , while vitamins C and e also act by increasing serum sod and gsh 10 and selenium by increasing glutathione peroxidase levels 25 . Zinc can also raise insulin-like growth factor (IgF) 1, known to be involved in bone formation 26 , although in VSMC the driver for calcification may be IGF-2 27 .…”
Section: Oxidative Stress CV Calcificationmentioning
confidence: 99%
See 1 more Smart Citation